Is location key?: an eye-tracking investigation of attention to nutrition information among young women and men - Johnson, Ashlie Nichole, author; Graham, Dan, advisor; Canetto, Silvia, advisor; Shomaker, Lauren, committee member (Colorado State University. Libraries, 2018)
Attention is a precursor for decision making and has been shown to be influential in the effective use of nutrition labels. Attention to nutrition information varies based on factors related to the individual, such as sex, and to the label, such as nutrient location. Given the previous findings that individuals tend to give more attention to the top portions of nutrition labels, this study used eye-tracking measures to explore whether moving three nutrients (sugar, fiber, and sodium) to higher positions on a label could increase attention and lead to healthier food choices. This study also sought to replicate previous findings of sex differences and over-reporting tendencies in label reading. Results from 112 undergraduate women (55.4%) and men showed that the novel label alteration had no significant effects on the attention to the moved nutrients or the healthfulness of subsequent food selections. No sex differences were found with regard to label reading, however, women had significantly higher rates of restrained eating and dieting behaviors (p<.015). Participants significantly over-reported their attention to sugar, but were accurate in predicting their low levels of attention to the other nutrients and to the label as a whole. The finding that sugar as a nutrient had distinct trends in this study highlights the need for future investigations aimed to distinguish potential nutrient-specific effects. Further research is needed to test the effectiveness of a greater variety of label formats using larger and more diverse samples.
Keywords: eye-tracking; nutrition labels; sex-differences; food selection; attention; over-reporting